Use of patency capsule in patients with established Crohn’s disease - Nemeth, Artur; Kopylov, Uri; Koulaouzidis, Anastasios; Wurm Johansson, Gabriele; Thorlacius, Henrik; Amre, Devendra; Eliakim, Rami; Seidman, Ernest G.; Toth, Ervin (Endoscopy, 2016)
Background and study aims: Video capsule endoscopy (VCE) is invaluable in the diagnosis of small-bowel pathology. Capsule retention is a major concern in patients with Crohn’s disease. The patency capsule was designed to evaluate small-bowel patency before VCE. However, the actual benefit of the patency capsule test in Crohn’s disease remains unclear. The aim of this study was to evaluate the clinical impact of patency capsule use on the risk of video capsule retention in patients with established Crohn’s disease.Patients and methods: This was a retrospective, multicenter study of patients with established Crohn’s disease who underwent VCE for clinical need. The utilization strategy for the patency capsule was classified as selective (only in patients with obstructive symptoms, history of intestinal obstruction or surgery, or per treating physician’s request) or nonselective (all patients with Crohn’s disease). The main outcome was video capsule retention in the entire cohort and within each utilization strategy.Results: A total of 406 patients who were referred for VCE were included in the study. VCE was performed in 132 /406 patients (32.5 %) without a prior patency capsule test. The patency capsule test was performed in 274 /406 patients (67.5 %) and was negative in 193 patients. Overall, VCE was performed in 343 patients and was retained in the small bowel in 8 (2.3 %). In this cohort, the risk of video capsule retention in the small bowel was 1.5 % without use of a prior patency capsule and 2.1 % after a negative patency test (P = 0.9). A total of 18 patients underwent VCE after a positive patency capsule test, with a retention rate of 11.1 % (P = 0.01). Patency capsule administration strategy (selective vs. nonselective) was not associated with the risk of video capsule retention.Conclusions: Capsule retention is a rare event in patients with established Crohn’s disease undergoing VCE. The risk of video capsule retention was not reduced by the nonselective use of the patency capsule. Furthermore, VCE after a positive patency capsule test in patients with Crohn’s disease was associated with a high risk of video capsule retention.